2021
DOI: 10.1002/ehf2.13760
|View full text |Cite
|
Sign up to set email alerts
|

A year in heart failure: an update of recent findings

Abstract: Major changes have occurred in these last years in heart failure (HF) management. Landmark trials and the 2021 European Society of Cardiology guidelines for the diagnosis and treatment of HF have established four classes of drugs for treatment of HF with reduced ejection fraction: angiotensin‐converting enzyme inhibitors or an angiotensin receptor‐neprilysin inhibitor, beta‐blockers, mineralocorticoid receptor antagonists, and sodium‐glucose co‐transporter 2 inhibitors, namely, dapagliflozin or empagliflozin. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 268 publications
(539 reference statements)
1
29
0
1
Order By: Relevance
“…[1] The risk is maximal for patients admitted with acute heart failure (AHF), reaching in-hospital mortality rates up to 10% and a composite of rehospitalisation and death rates around 30% at the one-year mark, depending on the series analysed. [2,3,4] New therapeutical options were made possible after the results of randomised trials with valsartan/sacubitril (Val/Sac) and SGLT₂ inhibitors were published. This has established solid proof of mortality reduction in both groups of patients with reduced and preserved ejection fraction (EF).…”
Section: Introductionmentioning
confidence: 99%
“…[1] The risk is maximal for patients admitted with acute heart failure (AHF), reaching in-hospital mortality rates up to 10% and a composite of rehospitalisation and death rates around 30% at the one-year mark, depending on the series analysed. [2,3,4] New therapeutical options were made possible after the results of randomised trials with valsartan/sacubitril (Val/Sac) and SGLT₂ inhibitors were published. This has established solid proof of mortality reduction in both groups of patients with reduced and preserved ejection fraction (EF).…”
Section: Introductionmentioning
confidence: 99%
“…Sex‐based differences exist among patients with HF 14–19 . Women with known or suspected coronary artery disease are at a higher risk of new‐onset HF, 20 but they are generally older than men at the time of diagnosis, more frequently develop HFpEF, and seem to have a better prognosis than men, even after age adjustment 21,22 .…”
Section: Epidemiologymentioning
confidence: 99%
“…The overall prevalence of HF ranges from about 1.5% to 4% in developed countries. [1][2][3] The HFA Atlas survey, conducted in 2018-2019 in 42 ESC countries, reported that the median incidence of HF was 3.20 [interquartile range (IQR) 2.66-4.17] cases per 1000 person-years, ranging from 1.99 in Italy and Denmark to 6.55 cases per 1000 person-years in Germany. 2,6 Women showed a higher prevalence of HFpEF compared with men.…”
Section: Epidemiologymentioning
confidence: 99%